A review on underutilized tropical fruits in Malaysia - Khoo, Hock Eng; Prasad, Krishnamurthy Nagendra; Kong, Kin Weng; Chew, Lye Yee; Azlan, Azrina; Sun, Jian; Ismail, Amin; Idris, Salma (Guangxi Academy of Agricultural Sciences, 2010)
Some non commercial seasonal and wild tropical fruits in Malaysia are less popular and sometimes grown locally for consumption and medicinal purposes. Their potential for rich polyphenolic compounds, carotenoids, anthocyanins, fatty acids, minerals, and amino acids is yet to be explored by the scientists. Malaysia has a rich diversity of tropical fruits which includes common, ornamental, rare, wild and highland fruits, but most of the indigenous fruits are considered to be underutilized. Typical underutilized fruits available in Malaysia are Asam, Bacang, Bambangan, Cerapu, Durian, Jambu, Kuini, Pulasan and Salak. These underutilized fruits are classified into 3 categories: species with potential for commercial development which mainly include Ara (Ficus sp.), Asam Gelugor (Garcinia atroviridis), Cempedak (Artocarpus integer), Ceri (Lepisanthes alata), Durian Hutan (Durio sp.), Kedondong/great hog plum (Spondias cytherea), Nangka/jackfruit (Artocarpus heterophullus), Pinang (Areca catechu), Pulasan (Nephelium ramboutan-ake), Salak (Salacca zalacca) and Sukun/breadfruit (Artocarpus altilis); species with possible development potential for local uses include Averrhoe bilimbi, Baccaurea motteyana, Baccaurea macrocrpa, Cynometra cauliflora, Dialum indum, Durio kutejensis, Garcinia hombroiniana, Garcinia parvifolia, Mangifera feotida, Phyllanthus emblica, Syzygium jambos; and species without current development potential for economic uses include Asam Kelubi (Salacca conferta), Bidara/Indian jujube (Zizyphus mauritiana), Jentik-Jentik (Baccaurea polyneura), Kundang (Garcinia parvifolia), Lengeng (Pometia sp.), Mertajam (Lepisanthes rubiginosa), Remia (Bouea microphylla), Sapote (Pouteria campechiana) and Sentol (Sandoricum koetjape). At present, the research on underutilized fruits is in nascent stage. There is definitely a need to make these fruits more popular and commonly available. Therefore, promotional campaign by government and private organizations for consumption of these underutilized fruits is need of the present time. Further studies are required to exploit their nutritional composition, antioxidant capability and therapeutic properties.